Influence of ingredient quality and diet formulation on amino acid digestibility and growth performance of poultry and swine - Dunmire, Kara Michelle (Kansas State University, 2022)
Ingredient varieties and heat processing applied to ingredients or complete diets can influence nutrient utilization for monogastric species and introduce variability in the final product sold for feed use or consumption. Thus, seven experiments were used in accomplishing the objective of this dissertation: to determine the influence of ingredient quality and diet formulation on amino acid (AA) digestibility and subsequent effects of growth performance for poultry and swine. First, the effects of using excessive thermal treatment of soy white flakes as a model for soybean meal (SBM) quality determined by official analytical methods and near infrared reflectance spectroscopy (NIRS) prediction equations was evaluated. Crushed soy white flakes (SWF) only exposed to mechanical pressing were ground and autoclaved at 128ºC for 0, 5, 10, 15, 30, 45, and 60 min at 200 kPa. Official analytical methods and NIRS were highly correlated for total Lys, available Lys, and Lys/CP. However, bias correction is needed to use the NIRS calibration set for SBM to predict SBM values from SWF. The next set of 3 experiments evaluated different soybean varieties with varying levels of crude protein (CP) when fed to broilers. Dietary treatments for these experiments consisted of 1 of 4 soybean sources varying in quality determined by CP content and processed into SBM. Two sources consisted of soybeans from a similar region and processed either commercially solvent extracted or experimentally solvent extracted. It was concluded that, broilers fed commercially processed SBM had improved AA digestibility compared to those fed experimentally processed soybeans from a similar region. Increasing CP content increased AA digestibility in both studies with no evidence for differences in high CP SBM and conventionally processed SBM. However, when broiler growth performance was evaluated, broiler performance was improved in broilers fed conventionally processed SBM compared to experimentally processed SBM. Within experimentally processed SBM treatments, when formulating diets using previously determined AA digestibility’s there was no evidence of difference in growth performance. The fifth study determined the influence of dietary fat and crystalline AA inclusion on broiler diet formulation and pellet quality. Dietary treatments consisted of a corn and SBM-based control, the control with crystalline valine (Val), and the control with crystalline Val and isoleucine (Ile). As crystalline AA increased in the diets, corn concentrations increased as SBM and the fat source were removed to balance for nitrogen-corrected metabolizable energy (MEn). Diets with increasing crystalline AA, Val, and Val + Ile, led to improved pellet quality which can be explained by the 0.4% or 0.6% reduction in added fat with increasing crystalline AA and balancing for MEn in the diet. The final two studies determined the effect of the pelleting process on diet formulations with varying levels of crystalline AAs and reducing sugars (RS) on digestibility and growth performance in growing pigs. Diets were formulated with low or high crystalline AA and low or high RS provided by co-product ingredients, DDGS and bakery meal. Digestibility and growth performance results concluded that pelleting diets with increased crystalline AA or RS did not affect from the pelleting response due to the Maillard reaction.
Keywords: Amino acids; Maillard reaction; Pelleting; Poultry nutrition; Soybean meal; Swine nutrition